Squamous Cell Carcinoma in the Third Eyelid of a Dog - Aléssio, Beatriz Crepaldi; Paula, Juliana Paniago Lordello de; Oliveira, Gustavo Gomes de; Caramalac, Silvana Marques; Souza, Alda Izabel de; Palumbo, Mariana Isa Poci; Babo-Terra, Veronica Jorge (Acta Scientiae Veterinariae, 2021)
Background: Squamous cell carcinoma is a malignant neoplasm that originates from the keratinized stratified squamous epithelium and predominantly affect light-skinned animals. In dogs, breeds such as American Staffordshire Terriers, white or speckled Bull Terriers, and Beagles have a higher predisposition. Squamous cell carcinoma presents in the skin, at slightly pigmented or hairy sites, especially in digits, but also may occur in the nasal planum, oral mucosa, and rarely, in the eye. Considering that few reports have been published on eye neoplasms, the aim of this paper is to describe a dog with a lesion in the third eyelid of his right eye which was diagnosticated with squamous cell carcinoma. Case: A 10-year-old male American Staffordshire dog was admitted to the Veterinary Medical Teaching Hospital of the Veterinary Medicine and Zootechnics College, Universidade Federal de Mato Grosso do Sul (UFMS), Campo Grande, Brazil with injury to the right eye. During the physical examination, there was also a non-adhered lump near the foreskin, measuring 1.5 cm in diameter. In addition, there was another lump in the third eyelid of the right eye, approximately 3 mm in diameter. Cytology of the dermal nodule was performed by fine-needle aspiration cytology; however, the sample was insufficient for cytological evaluation. Therefore, the animal was placed under general anesthesia for skin lump excision and for fine-needle aspiration cytology of the third eyelid nodule. The histopathological exam revealed high cellularity of epithelial cells, intense anisocytosis and pleomorphism, cytoplasmic basophilia and vacuolation, multiple evident nucleoli, and anisocariosis and coarse chromatin. These finds were compatible with squamous cell carcinoma, which was the same result suggested by fine-needle aspiration cytology of the third eyelid sample. Based on these results, the dog underwent a surgical procedure for enucleation and subsequent histopathological evaluation of the nodule in the third eyelid, which confirmed the squamous cell carcinoma diagnosis. Discussion: Squamous cell carcinoma is an extremely aggressive tumor with low metastatic potential, characterized by invasion of the dermis by proliferation of malignant epithelial cells from the prickly layer. It is most common in elderly animals, and American Staffordshires are among the breeds that are predisposed to develop this tumor. The clinical presentation is highly variable, depending on the tissue involved. In this case, the dermal nodule was an elevated area on the skin and the third eyelid nodule resembled an ulcerative mass. Cytological examination from the lesion located on the third eyelid, showed malignancies cytoplasmic changes frequently found in carcinomas such as anisocytosis, cytoplasmic basophilia, and cell pleomorphism. In addition, nuclear changes had also occurred, such as crass chromatin, multiple evident nucleoli, and multinucleated cells. A presumptive diagnosis was made based on cytology and was confirmed after biopsy and histopathological examination. Because it is uncommon in dogs, squamous cell carcinoma of the third eyelid may be misdiagnosed, delaying correct treatment, and accelerating the development of the tumor. Currently, various therapeutic approaches are available, such as surgical excision, electrosurgery, cryosurgery, radiation, and hyperthermia. The choice of treatment depends on the location and stage of the lesions. Surgical treatment should be aimed at removing sufficient tissue to leave surgical margins free of neoplastic cells.